2013
DOI: 10.1186/1742-4755-10-56
|View full text |Cite
|
Sign up to set email alerts
|

Median ages at stages of sexual maturity and excess weight in school children

Abstract: BackgroundWe aimed to estimate the median ages at specific stages of sexual maturity stratified by excess weight in boys and girls.Materials and methodThis was a cross-sectional study made in 2007 in Florianopolis, Brazil, with 2,339 schoolchildren between 8 to 14 years of age (1,107 boys) selected at random in two steps (by region and type of school). The schoolchildren were divided into: i) those with excess weight and ii) those without excess weight, according to the WHO 2007 cut-off points for gender and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The sampling procedure is described in detail elsewhere [20][21][22][23]. Briefly, for sample size calculation, the following parameters were assumed: excess weight prevalence of 22.1% for children aged 7-10 years [24] and 12.6% for those aged 11-14 years [25]; acceptable error of 3 percentage points; two-tailed test; confidence level of 95%; design effect of 1.5; and an addition of 10% for losses.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling procedure is described in detail elsewhere [20][21][22][23]. Briefly, for sample size calculation, the following parameters were assumed: excess weight prevalence of 22.1% for children aged 7-10 years [24] and 12.6% for those aged 11-14 years [25]; acceptable error of 3 percentage points; two-tailed test; confidence level of 95%; design effect of 1.5; and an addition of 10% for losses.…”
Section: Methodsmentioning
confidence: 99%
“…Although several other studies have examined the association between sexual maturation status and obesity [15, 17, 24, 25], few studies have related sexual maturation to adiposity indicators. To our knowledge, this is one of the first studies to analyze the influence of sexual maturation status on the relationship between increased body adiposity and age in Brazilian children.…”
Section: Discussionmentioning
confidence: 99%
“…The final sample consisted of 2506 schoolchildren in 2012 (87% of 2880 students). The sampling procedure is described in detail elsewhere (D'Avila et al, 2016; Luciano et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…IBGE, 2010). Previous studies in schoolchildren from Florianópolis , a city in the Southern Brazil, have demonstrated an increase in the prevalence of overweight (including obesity) from 2007 (34.4% for boys and 24.0% for girls) (Luciano et al, 2013) to 2012 (37.6% for boys and 29.0% for girls) (Corrêa et al, 2018).…”
Section: Introductionmentioning
confidence: 98%